Endoscopic Findings of Dyspeptic Patients and H. pylori infection in patients at a Tertiary care Teaching Hospital, Nepal (Janaki Medical College Journal of Medical Science, 2023)
Introduction: Dyspepsia is a common condition presenting with epigastric pain that lasts at least a month and may develop peptic ulcers. Helicobacter pylori infection and lifestyle are the risk factors for peptic ulcers. So, the objective of this study was to identify the magnitude and status of Helicobacter pylori in dyspeptic patients.Material and Methods: This cross-sectional study included data from the endoscopy unit records among patients who had endoscopy for dyspepsia and biopsy taken from an antrum for the helicobacter pylori status, during June 1, 2020 and November 30, 2022 at Manmohan Memorial Medical College Teaching Hospital, Kathmandu, Nepal. Age, sex and status of histopathology findings were analyzed for association using Chi-square test and a p 60 y) with p-value